Correction: Zheng et al. Fabrication of Co-Assembly from Berberine and Tannic Acid for Multidrug-Resistant Bacteria Infection Treatment. Pharmaceutics 2023, 15, 1782 - Tingting Zheng; Huan Chen; Chenyang Wu; Jinrui Wang; Mengyao Cui; Hanyi Ye; Yifan Feng; Ying Li; Zhengqi Dong (Pharmaceutics)
In the original publication [...]